Numerical Solutions to Fractional Perturbed Volterra Equations - B. Bandrowski; A. Karczewska; P. Rozmej (Abstract and Applied Analysis)
In the paper, a class of perturbed Volterra equations of convolution type with three kernel functions is considered. The kernel functions , , , correspond to the class of equations interpolating heat and wave equations. The results obtained generalize our previous results from 2010.